TRAUMA MASAKECIL SEPERTITERGAMBARDALAM FILM â€˜JOKERâ€™ PRODUKSIWARNER BROS (2019) - Sudarwanto, Pricillia Ayu Pratiwi; Wantasen, Isnawati L.; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â This research is entitled â€œChildhood Trauma as Reflected in The Film Joker by Warner Bros 2019â€. The aims of this research are to identify and classify the main character who experiences childhood trauma in the film, and this research focused on childhood trauma conditions from the main character by using a psychological approach. The writer uses three theories from Horney (1939), Wolfe (1999), and Stanton (1965) in the process of identifying, classifying, and analyzing related to childhood trauma and characters. The method used in this study is a descriptive method. In doing this research, the writer watches the joker film, reads joker script, some journals and book. The data were collected by the writer from joker film and its script, related to character's speech, character conduct, character conversation and character action. The result of this research shows that there are four types of childhood trauma that happened to the main character, namely physical abuse, child neglect, sexual abuse, and emotional abuse. The writer hopes that this research could enrich psychological research in literature, and can make anyone understand the causes and ef ects of childhood trauma experiences.Keywords: Childhood Trauma, Child Abuse, Film Joker, Character Development, Psychology Analysis.